The Efficacy of the SECI Model for the Training of High School Teachers in Relation to Gender Equality in Vietnam - Dung, Mai Thi Thuy; Brundrett, Mark (VNU Journal of Science: Education Research; Vol 37 No 4DO - 10.25073/2588-1159/vnuer.4530, 2021)
Vietnamese government policy has been one of complete equality of opportunity in schools and in wider society, both as a commitment to social justice and as a way of enhancing the economy of the nation by facilitating and encouraging much greater inclusion of women in economic activity. One of the main aims of the research reported in this article was to trial programmes of training for teachers and teacher education students about gender equality in education using the model of Socialisation, Externalisation, Combination and Internalisation (SECI), first developed in Japan, which integrates knowledge acquisition with social learning activities (Nonaka and Takeuchi, 1995). The response to the programme of training using the SECI model was positive, suggesting that this approach may be an effective model for both Initial Teacher Education and Continuing Professional Development for High School Teachers in Vietnam.